A NOTE REGARDING SOME FUZZY SSPO MAPPINGS - Makolli, Shkumbin; Krsteska, Biljana (Matematichki Bilten, 2023)
In this paper we will introduce the concept of fuzzy SSPO irresolute continuous mappings, fuzzy SSPO irresolute open (closed) mappings as well as the concept of SSPO homeomorphism. We will also study some of their properties and their relation with other forms of fuzzy continuity.